City categories and their position in polish local self-government system - Obrębska, Marta; Wróbel, Sylwester (Political Preferences, 2016)
This study offers a short introduction to the development of cities in general, their types, functions, position and points of differentiation. It stresses the importance of multifarious factors that determine the importance of particular entities. The main part of the study though is concerned with Polish cities. It takes into consideration their origins, geographical location, administrative and political importance, city reforms, demographic and economic factors as well as their functions and finance to assess the role and salience of different city categories. It analyses the impact of the aforementioned factors, especially of administrative and self-government reforms on the position of the cities in Polish self-government system. It also finds that the self-government reforms, reflecting the international trend towards the unification of self-government system, have not led to the homogenization of cities in Poland, but that provisions introduced allow for individualisation of their internal structures and functions. Key words: city, self-government, Poland, city- a history